Behavioral factors influencing partner trust in logistics collaboration: a review - Morice Daudi; Jannicke Baalsrud Hauge; Klaus-Dieter Thoben (Logistics Research, 2016)
Logistics collaboration has emerged a prevalent strategy to mitigate challenge individuals and organizations encounter. A successful collaboration, however, depends on certain trustworthy behaviors partner exhibit. To that end, understanding aspects constituting behavioral uncertainty and mechanisms by which such aspects affect partner trust is a necessary. This necessity counts on emergent behavioral trust uncertainties, constituted by partner's actions and interactions occurring during collaboration. While this is a necessary requirement, most of the studies in the literature lack to take into account the influence of behavioral uncertainty on collaboration and partner trust. To that effect, this paper uncovers outlined limitation by establishing behavioral factors influencing partner trust in operational stage of logistics collaboration. To accomplish this objective, a systematic literature review (SLR) is deployed to consolidate research domains of logistics, supply chain, collaboration, and trust. SLR proceeds by defining a review protocol, followed by a search process conducted in 5 databases using 20 search terms on articles published between 2001 and 2015 inclusively. Among findings this SLR has revealed are four behavioral factors and thirteen criteria proposed to affect partner trust. Additionally, these factors constitute success and measurable criteria needed for empirical investigation which may employ experimental and/or case-study methods. Moreover, synthesized factors extend further an understanding of behavioral trust in ad hoc collaborative networks, a large part of which being supported by networks of humans and computers.
Keywords: 650; Trust; Partner trust; Resource sharing; Behavioral trust; Logistics collaboration